Respuesta :

1/4(-3n + 3/2) =
-3/4n + 3/8

Answer:

 [tex]\frac{1}{4}(-3n+\frac{3}{2})[/tex] is [tex]\frac{-6n+3}{8}[/tex]      

Step-by-step explanation:

Given that: [tex]\frac{1}{4}(-3n+\frac{3}{2})[/tex]                  ......[1]

The distributive property says that:

[tex]a.(b+c)=a.b+a.c[/tex]

Apply distributive property on [1] we have;

[tex]=\frac{1}{4}.(-3n)+\frac{1}{4}.\frac{3}{2}[/tex]    

Simplify:

[tex]=\frac{-3n}{4}+\frac{3}{8}[/tex]    

[tex]=\frac{-6n+3}{8}[/tex]    

Therefore, the expression that shows the result of applying the distributive property to  [tex]\frac{1}{4}(-3n+\frac{3}{2})[/tex]  is  [tex]\frac{-6n+3}{8}[/tex]